Influence of Weakening Groove on Cutting Results of Composites Subjected to Shaped Charge Jet - Mingfa Ren; Fei Weng; Jing Sun; Ke Tang; Lina Feng; Rong Chen (Shock and Vibration)
Carbon-fiber-reinforced polymer (CFRP) has been widely used in aerospace structures for its high strength to weight ratio and high stiffness to weight ratio. However, current pyrotechnic separation devices are mainly made of metal materials, the cutting research on CFRP composites is limited, and the effect of weakening groove on cutting results of composites is unclear under the action of shaped charge jet. In this paper, there firstly established a three-dimensional model of explosive cutting of CFRP composites by nonlinear finite element analysis (FEA), and based on the separation time, delamination, and kinetic energy of the laminate, the influence of weakening grooves on cutting results to the laminate is discussed. The results show that, in contrast to laminates with weakening grooves, laminates without weakening grooves increase the delamination of laminates. At the same time, here, we carried out the explosive cutting test on CFRP composites to verify the rationality of the simulation model. In addition, in order to obtain a better model under the action of shaped charge jet, we optimized the width and height of weakening groove by simulation calculation. Therefore, it proves that this study can guide the application of CFRP composites subjected to shaped charge jet in aerospace separation engineering.